SIRATAR PERANCANGAN SISTEM PENERANGAN JALAN PINTAR TENAGA SURYA BERBASIS IOT - TIKA AMBAR SARI, ARIF SETYO WAHYUDI (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
Solar street lighting can be a solution to solve these problems and can utilize solar energy. Solar street lighting is street lighting that utilizes sunlight as a source of electrical energy. In system design, there are several components, namely sensors and the addition of a microcontroller as a regulator of street lighting performance. At the implementation stage, this system is placed on a road with less light, from this stage the results obtained that the sensor coverage area can read as far as 6 meters with a reading angle of 200o the impact of the implementation of this designed system in the field of technology/innovation is better than previous tools within the range of the PIR sensor. In the social and environmental fields, the devices used such as solar panels are able to save on the use of electrical energy because they utilize natural energy, namely the sun. Providing solutions to the community in the event of a power outage, this lighting system will not die, so that at any time it is able to illuminate the community when walking at night.